THE INFLUENCE OF WORK ENVIRONMENT AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE IN THE ENVIRONMENT AND FORESTRY SERVICE OF NORTH SUMATRA PROVINCE - Nilfaujia; Bahktiar; Ismail Nst (CV. RADJA PUBLIKA, 2025)
The purpose of this study is to explain whether there is a positive influence between the work environment and work motivation on employee performance at the Environmental and Forestry Service of North Sumatra Province, Medan. In addition, this study is also intended to determine the condition of the Work Environment and Work Motivation on employee performance at the Environmental and Forestry Service of North Sumatra Province, Medan. Research on the work environment and work motivation on employee performance at the Environmental and Forestry Service of North Sumatra Province, Medan with the type of research used in this study is descriptive and verification using the Explanatory Survey research method. The author uses quantitative research techniques, because the research conducted is related to statistical tools to process the results of the questionnaire so that it can be known whether or not there is an influence between the work environment and work motivation on employee performance at the Environmental and Forestry Service of North Sumatra Province, Medan. The data analysis method used in this study is The data analysis technique used is multiple regression. The results of the study 1) Work environment on employee performance at the Environmental and Forestry Service of North Sumatra Province, Medan. From the calculation results obtained 0.482 or 48.2% Work environment on performance. 2) Work motivation on employee performance with a result of 0.596 or 59.6%. 3) The magnitude of the influence of the work environment and work motivation together on the performance of employees of the Environment and Forestry Department of North Sumatra Province Medan is 0.865 or 86.5% while the remaining 13.5% is influenced by other variables not tested in this study.